Photoinactivation of single and mixed biofilms of Candida albicans and non-albicans Candida species using Phorodithazine - Carmello, Juliana Cabrini [UNESP]; Alves, Fernanda [UNESP]; Oliveira Mima, Ewerton Garcia de [UNESP]; Jorge, Janaina Habib [UNESP]; Bagnato, Vanderlei Salvador; Pavarina, Ana Claudia [UNESP] (Elsevier B.V., 2017)
This study evaluated the effectiveness of antimicrobial photodynamic therapy (aPDT) mediated by Photodithazine (R) (PDZ) formulated in hydrogel, in the inactivation of mono and duo-species biofilms of Candida albicans, Candida glabrata and Candida tropicalis. Standardized suspensions of each strain were prepared and after biofilm formation, mono-species were treated with 150 and 175 mg/L of PDZ for 20 min (pre-irradiation time), and exposed to LED light at a dose of 37.5 J/cm(2) (660 nm). The duo-species biofilms (C. albicans + C. glabrata and C. albicans + C. tropicalis) were treated with 150 mg/L of PDZ and light. Additional samples were treated with PDZ or light only, and the control did not receive any treatment. Next, microbiological evaluation was performed by spreading the cells on Sabouraud Dextrose Agar and CHROMagar Candida for colony forming units (CFU/mL). Moreover, the total biomass of biofilm was verified using the crystal violet staining assay (CV). The data were submitted to ANOVA and Tukey post-hoc (alpha = 0.05). The use of PDZ 150 mg/L promoted a reduction of 1.0, 1.2, 1.5 log(10) in the viability of C glabrata, C. albicans and C. tropicalis, respectively. The same concentration reduced in 1.0 log(10) the viability of each species grown as duo-species biofilms. The crystal violet assay showed that the use of 150 mg/L reduced 24.4%, 39.2% and 43.7% of the total biomass of C albicans, C tropicalis and C. glabrata, respectively. aPDT did not reduce the total biomass to the duo-species biofilms. Thus, PDZ-mediated aPDT was more effective in the inactivation of mono-species biofilms of Candida spp. compared with duo-species biofilm. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Photodynamic therapy; Candida species; Photosensitizer agent